Reinventing Government through HRM strategies - Adhia , Hasmukh (Haderabad, 2007)
The book covers analytical presentation of some innovative strategies adopted by Government of Gujarat for training and motivation of its staff, which became quite successful in changing the mindset of Government employees.
Keywords: Human resource management-Government-Gujarat